2011
DOI: 10.15666/aeer/0902_157166
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Plant Diversity and Productivity in Natural and in Managed Grasslands

Abstract: Assaf et al.: The relationship between plant diversity and productivity in natural and in managed grasslands - Abstract. Despite the fact that several experiments have been conducted to explore the biodiversityproductivity relationship in synthesized and natural plant communities, the results obtained were contradictory and no clear consensus has been reached. Recent experiments that surveyed mature natural plant communities have investigated this relationship across environmental gradients, where biotic and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
3
16
0
1
Order By: Relevance
“…b). This result is consistent with findings in grasslands where species identity and species evenness have been put forward to explain the relationship between productivity and diversity (Wilsey & Potvin ; Assaf, Beyschlag & Isselstein ). On average, the three mixed stands in highlands, European beech–Norway spruce, European beech–silver fir and to a lesser extent, silver fir–Norway spruce mixtures overyielded (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…b). This result is consistent with findings in grasslands where species identity and species evenness have been put forward to explain the relationship between productivity and diversity (Wilsey & Potvin ; Assaf, Beyschlag & Isselstein ). On average, the three mixed stands in highlands, European beech–Norway spruce, European beech–silver fir and to a lesser extent, silver fir–Norway spruce mixtures overyielded (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Species evenness describes how uniform the population sizes of the different species in a community are and, together with species richness, determines a community's species diversity (Smith and Wilson 1996). The first experiments on the influence of species evenness on ecosystem processes are relatively recent (Wilsey and Potvin 2000, Wilsey and Polley 2002, Mattingly et al 2007) and the debate on the effects of evenness on ecosystem functioning still continues today (Assaf et al 2011, Schmitz et al 2013, Rohr et al 2016), due to differences in methodology and practical limitations of testing species evenness effects at high richness levels in experiments (Naeem 2009). Indeed, because the number of different communities that are required to manipulate species evenness becomes excessive once there are more than just a few species, studies on synthesized communities have only rarely expanded to more than four plant species (Wilsey and Potvin 2000, Kirwan et al 2007, Mattingly et al 2007, Wittebolle et al 2009, Schmitz et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…In grassland experiments with low ground cover, biodiversity still conferred stability but productivity depended more on ground cover than on species richness [65]. Also, experiments in Germany by Assaf et al [66] suggest that biodiversity has a stronger effect on productivity in unmanaged than in managed grasslands. De Boeck et al [67] found by experiment that warming may increase the detrimental effect of species loss on grassland productivity in temperate climates.…”
Section: Data and Inferences From Experimental And Observational Studiesmentioning
confidence: 98%